Reduction of Nε-(carboxymethyl) lysine by (−)-epicatechin and (−)-epigallocatechin gallate: The involvement of a possible trapping mechanism by catechin quinones. (15th November 2018) - Li, Yuting; Li, Lin; Lund, Marianne N.; Li, Bing; Hu, Yi; Zhang, Xia
Highlights: Catechins inhibit N ε -(carboxymethyl)lysine formation under food processing conditions. (−)-Epicatechin eliminates free N ε -(carboxymethyl)lysine in heated coconut milk. Catechin quinones trap N ε -(carboxymethyl)lysine under alkaline condition. Abstract: (−)-Epicatechin (EC) and (−)-epigallocatechin gallate (EGCG) (0.001–5%) were found to reduce N ε -(carboxymethyl) lysine (CML) concentrations by up to 0.80 ± 0.11 mM and 0.85 ± 0.07 mM, respectively, as quantified by HPLC-MS during heating at 80 °C and 100 °C in a glucose-lysine model system at pH 5, 7 and 8, which mimic different food processing conditions. With the addition of 1 mM EC, the free CML concentration in coconut milk was reduced to 5.7 ± 0.1 μg/mL (∼2.8 × 10 −2  mM), which was significantly lower than that in unheated coconut milk (6.1 ± 0.2 μg/mL (∼3.0 × 10 −2  mM), p < 0.05) indicating that the free CML may be eliminated by the addition of EC in coconut milk. Products of EC/EGCG quinones reacted with CML by a Michael addition or Schiff base addition in model systems were tentatively identified by UPLC-ESI-MS/MS.